Penerapan Model Pembelajaran Kooperatif Tipe Examples Non Examples dengan Pencitraan Terpandu dalam Peningkatan Minat, Aktivitas, dan Hasil Belajar IPA Biologi Siswa - Anastasia Dwiani Andhyka Putri; Jekti Prihatin; Mr Suratno (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2015)
Teachers as educators must be able to plan and manage learning and create a learning environment that is comfortable and attractive, so students interest to be actively involved in the learning process. High interest and actively involvement of students in the learning process will help students understand the material being studied and will be able to improve learning outcomes. The implementation of cooperative learning model examples non examples can be applied in the process of learning science Biology in material damage and environmental pollution to increase interest, activities, and learning outcomes Biological Science VIIA grade students at SMP Negeri 3 Nganjuk. The research method used is a CAR (Classroom Action Research) with the researcher asa teacher educator. Results obtained from the study is an increase in interest from 72.50% to pre-cycle of 82.67% in the post-cycle with high criteria. Learning activities also increased from 71.76% pre-cycle, and 83.58% in the post-cycle with high activity criteria. Interest and learning activities that increase was followed by an increasing in student learning outcomes initially studied classical completeness only 62.16% to 78.38% in the post-cycle. The results obtained show that the implementation of cooperative learning model examples non examples can increase interest, activities, and student learning outcomes in the class VIIA SMP Negeri 3 Nganjuk. Keywords: interest, activity, learning achievement, examples non examples type, guided imagery